2016
DOI: 10.1128/jvi.01904-15
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Mutations Acquired in Refrex-1, a Restriction Factor against Feline Retroviruses, during its Cooption and Domestication

Abstract: Endogenous retroviruses (ERVs) are remnants of ancestral retroviral infections of germ cells. Retroviral endogenization is an adaptation process for the host genome, and ERVs are gradually attenuated or inactivated by mutation. However, some ERVs that have been "domesticated" by their hosts eventually gain physiological functions, such as placentation or viral resistance. We previously reported the discovery of Refrex-1, a soluble antiretroviral factor in domestic cats that specifically inhibits infection by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…Inspection of the hsaHTenv and orthologous env sequences in gorillas and orangutans revealed mutations at the site where proteolytic cleavage by furin-like proteases generates surface (SU) and transmembrane (TM) subunits (Hallenberger et al, 1992) (Figure 4E). Insertion of these cleavage site mutations into ancHTenv abolished cleavage and pseudotype infection, while reversion of mutations in hsaHTenv did not correct the cleavage defect and did not yield infectious MLV particles (Figure 4—figure supplement 1), Thus, loss of HERV-T envelope function by hsaHTenv was a multi-step process, including loss of furin cleavability, similar to findings with feline endogenous retroviral Env proteins (Ito et al, 2016).
10.7554/eLife.22519.012Figure 4.The human genome encodes a HERV-T Env ORF that does not function as a retroviral envelope.( A ) Infectiousness of MLV particles pseudotyped with untagged or C-terminally HA-tagged ancHTenv or hsaHTenv (Mean ± SD, n = 3 replicates, one of two experiments).
…”
Section: Resultssupporting
confidence: 51%
“…Inspection of the hsaHTenv and orthologous env sequences in gorillas and orangutans revealed mutations at the site where proteolytic cleavage by furin-like proteases generates surface (SU) and transmembrane (TM) subunits (Hallenberger et al, 1992) (Figure 4E). Insertion of these cleavage site mutations into ancHTenv abolished cleavage and pseudotype infection, while reversion of mutations in hsaHTenv did not correct the cleavage defect and did not yield infectious MLV particles (Figure 4—figure supplement 1), Thus, loss of HERV-T envelope function by hsaHTenv was a multi-step process, including loss of furin cleavability, similar to findings with feline endogenous retroviral Env proteins (Ito et al, 2016).
10.7554/eLife.22519.012Figure 4.The human genome encodes a HERV-T Env ORF that does not function as a retroviral envelope.( A ) Infectiousness of MLV particles pseudotyped with untagged or C-terminally HA-tagged ancHTenv or hsaHTenv (Mean ± SD, n = 3 replicates, one of two experiments).
…”
Section: Resultssupporting
confidence: 51%
“…ERV-DC10 and ERV-DC18 are the first feline ERVs that were identified as replication-competent proviruses residing within the host genome (32,60,61). In this study, we newly identified ERV-DC14 as another replication-competent ERV and characterized this virus in detail.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study demonstrated that ERV-DC14 did not interfere with ERV-DC10, indicating that these viruses use different viral receptors (29,32). In this study, we compared the host ranges of ERV-DC14 and ERV-DC10 in detail by using the ERV-DC14TA mutant so that it would be easier to monitor viral infection.…”
Section: Erv-dc14 and Erv-dc10 Tropismmentioning
confidence: 99%
“…Because it was unclear how ERV-DC7 and ERV-DC16 evolved into Refrex-1, we investigated the process of Refrex-1 evolution using the reconstructed full-length env genes of ERV-DC7 and ERV-DC16 (ERV-DC7fl and ERV-DC16fl, respectively) [ 50 ]. An infectivity analysis of ERV-DC7fl and ERV-DC16fl revealed that they are unable to produce viruses because the cleavage between SU and TM is disrupted.…”
Section: Refrex-1 Is Under Robust Control By Accumulated Inactivatmentioning
confidence: 99%